2019
DOI: 10.1002/ardp.201900007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and in vitro effect of the Cu(II) complex with niflumic acid and 3‐picoline on paraoxanase‐I

Abstract: Niflumic acid is used to treat inflammatory rheumatoid diseases, pain, and fever. The present study reports the experimental, spectroscopic, thermal, structural analyses, and biological activities of this complex. The nonsteroidal anti-inflammatory drug niflumic acid, 3-picoline, and copper(II) chloride were utilized to synthesize a new complex: [Cu 2 Cl 2 (nif) 2 (3-pic) 4 ]. The crystal structure of [Cu 2 Cl 2 (nif) 2 (3-pic) 4 ] was determined by X-ray crystallography. The complex crystallizes in the tricli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…We have found that these complexes inhibit the PON1 enzyme. K i values (0.057–0.212 mM) obtained in present study were more effective than K i values (0.116–0.434 mM) in our previous studies . Furthermore, Alim and Beydemir investigated in vitro interactions between the PON1 enzyme and some sulfonamides.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…We have found that these complexes inhibit the PON1 enzyme. K i values (0.057–0.212 mM) obtained in present study were more effective than K i values (0.116–0.434 mM) in our previous studies . Furthermore, Alim and Beydemir investigated in vitro interactions between the PON1 enzyme and some sulfonamides.…”
Section: Discussionsupporting
confidence: 43%
“…Complex 3 and 4 showed less inhibition activity than 1 and 2 complexes, with K i of 0.155 and 0.212 mM, respectively. Complex 1–4 showed more inhibitory effect compared with recently reported PON1 inhibitors in the literature . Effects of different copper(II) complexes, which are derived dicarboxylic acid and naproxen, for PON1 enzyme have been researched until now by our group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The whole PON1 activity procedure was performed according to our previous studies [10,17]. Briefly, Paraoxonase activity of PON1 has been investigated with paraoxone (1 mM) in 50 mM glycine-NaOH (pH 10.5) buffer including 1 mM CaCl2 at 25°C.…”
Section: Pon1 Activity Assaymentioning
confidence: 99%